1
$\begingroup$

Suppose that $f$ satisfies the Lipschitz condition.

For given initial values $y_0, z_0\in \mathbb{R}$, we consider the IVPs: $$y'=f(t,y), \ y(a)=y_0 \\ z'=f(t,z), \ z(a)=z_0$$ with $a\leq t \leq b$.

$$$$

1) Show that the problem has unique solution, i.e. if $y_0=z_0$ then $y(t)=z(t)$ for all $t$. $$\max_{1\leq t\leq b}|y(t)-z(t)|\leq c|y_0-z_0|$$

2) Let $\{y^n\}$ and $\{z^n\}$ be aproximation of the problem that we get by the mean value method, let $$\epsilon^n:=y^n-z^n \\ \epsilon^{n+1/2}:=y^{n+1/2}-z^{n+1/2} \\ y^{n+1/2}=\frac{1}{2}(y^{n+1}+y^n)$$ show that $$(\epsilon^{n+1}-\epsilon^n)\epsilon^{n+1/2}=h[f(t^{n+1/2}, \frac{1}{2}(y^{n+1}+y^n))-f(t^{n+1/2}, \frac{1}{2}(z^{n+1}+z^n))]\epsilon^{n+1/2}$$

$$$$

I have done the following:

1) I have shown that $e^{-2Lt}(y(t)-z(t))^2$ is descreasing for $t\in [a,b]$.

Then we have the following: $$0\leq e^{-2Lt}(y(t)-z(t))^2\leq e^{-2Lt_0}(y(t_0)-z(t_0))^2=e^{-2Lt_0}(y_0-z_0)^2$$ If $y_0=z_0$ we get $e^{-2Lt}(y(t)-z(t))^2=0 \Rightarrow y(t)-z(t)=0\Rightarrow y(t)=z(t)$$ Therefore the problem has a unique solution.

For the inequality we can show that $y(t)-z(t)$ is decreasing, but then it follows that $|y(t)-z(t)|\leq |y_0-z_0|$, but how do we get that constant $c$ at the right side?

2) For this one I don't really have an idea. Could yyou give me a hint?

$\endgroup$
2
  • 1
    $\begingroup$ In 2), what is the meaning of "approximation", is it a sequence of functions or the result of some numerical method? And what is the "mean value method"? Is it the implicit midpoint method? $\endgroup$ Aug 29, 2019 at 12:54
  • $\begingroup$ It is meant the result of a numerical method.. @LutzL $\endgroup$
    – Mary Star
    Aug 29, 2019 at 13:24

1 Answer 1

1
$\begingroup$

By the definition of the implicit midpoint method, you directly have \begin{align} y^{n+1}-y^n&=hf(t^{n+1/2},y^{n+1/2})\\ z^{n+1}-z^n&=hf(t^{n+1/2},z^{n+1/2})\\ \end{align} so that in the difference of both equations you get without any further transformation $$ ϵ^{n+1}-ϵ^n=h[f(t^{n+1/2},y^{n+1/2})-f(t^{n+1/2},z^{n+1/2})]. $$ Now simply multiply with $ϵ^{n+1/2}$ to get the claimed equation.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.